Dog’s ownership. Benefits for the physical health of middle-aged patients with Type 2 Diabetes Mellitus - Hugues Hernandorena, Beatriz (2018)
The possession of companion dogs exerts benefits on the physical health (blood pressure, heart rate) in people. Patients with diabetes mellitus type 2 (DM2) of middle age often suffer from these alterations so that the possession of these animals could contribute to the control of their disease. In order to describe some clinical variables (blood pressure and heart rate) anthropometric (body mass index and waist circumference), glycaemic control (glycosylated haemoglobin) in persons with DM2, and the effects of dog’s ownership on aspects of personal satisfaction, the control of DM2 and the motivations for carrying out physical activities, a descriptive, cross-sectional, quantitative study was carried out that included 24 patients with dogs and 24 without them, who were attended at the Diabetic Care Centre of Havana, Cuba. Better health indices were obtained in the group that had dogs as pets, who also showed great personal satisfaction, positive effects on glycaemic control and motivations for carrying out physical activities from holding.